Courts and sovereign eurobonds: Credibility of the judicial enforcement of repayment - Issam Hallak (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
While focusing on the protection of distressed sovereigns, the current debate intended to reform the International Financial Architecture has hardly addressed the protection of creditors rights that varies among laws. I suspect however that this constitutes an essential determinant of the success of suggested solutions, especially under the contractual approach. Based on a sample of bonds issued by developing countries states in the period, January 1987 to December 1997, I find that, for given contract characteristics (e.g. listing markets and currency), the governing law is selected according to its ability to enforce repayment. However, although the New York law seems looser and incur larger enforcement costs than the England&Wales law, the former permits equivalent yearly credit amounts. I interpret this as a consequence of the existence of a larger set of valuable assets (e.g. trade) in the US that constitute implicit securities. My findings yield important implications for the reforms. In particular, provided that there exists a seemingly equivalent enforcement credibility between England and New York laws, the prompt implementation of the contractual approach solution should constitute a valuable first step toward efficient sovereign debt markets.
urn:nbn:de:hebis:30-10397
Keywords: F34; G33; K33; 330; Law and Finance; Sovereign Debt Restructuring Mechanism; Collective Action Clause; Bankruptcy; Creditor Rights Protection